2017
DOI: 10.1159/000466712
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Patterns of <b><i>SOX3, SOX9</i></b>, and <b><i>WNT4</i></b> Genes in Gonads of Dogs with XX (<b><i>SRY</i></b>-Negative) Disorder of Sexual Development

Abstract: Ovotesticular or testicular disorder of sexual development in dogs with female karyotype and lack of SRY (XX DSD) is a common sexual anomaly diagnosed in numerous breeds. The molecular background, however, remains unclear, and epigenetic mechanisms, including DNA methylation, have not been studied. The aim of our study was comparative methylation analysis of CpG islands in promoters of candidate genes for XX DSD: SOX9, SOX3, and WNT4. Methylation studies were performed on DNA extracted from formalin-fixed/para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recently, significantly higher methylation of SOX3 gene [30] has been reported in both the ovotesticular and the testicular canine XX DSD. In mice, it has been shown that SOX3 can replace SRY and drive the differentiating gonad towards a female fate [63].…”
Section: Gain Of Function Of Sox9mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, significantly higher methylation of SOX3 gene [30] has been reported in both the ovotesticular and the testicular canine XX DSD. In mice, it has been shown that SOX3 can replace SRY and drive the differentiating gonad towards a female fate [63].…”
Section: Gain Of Function Of Sox9mentioning
confidence: 99%
“…Besides, as such loss of function would also enhance testosterone synthesis, the increased secretion of androgens could explain the partial masculinization of genital ducts, and the development of epididymides and deferens ducts in XX;SRY-negative individuals [67]. Studies on the methylation of WNT4 gene showed that methylation was similar in XX DSD and control dogs [30], suggesting that this may not be an adequate candidate gene for the XX DSD syndrome in dogs. Still, a decreased transcription of WNT4 was reported in XX DSD embryos using a genome wide association study and whole genome sequencing [13].…”
Section: Loss Of Function Of Wnt4/rspon1/-catenin and Foxl2 Pathwaysmentioning
confidence: 99%
“…Although until today, the molecular background of XX DSD (78, XX; SRY-negative) is not fully recognized, it is assumed to be linked to the copy number variation (CNV) in the region harbouring the SOX9 gene. Rossi et al (2014) and Switonski (2017) showed that methylation of SOX3 promoter region may play a role in canine XX DSD pathogenesis. As reported by Gonen et al (2018), the regulatory region of SOX9 is complex and that a single far-upstream 557-base pair element (Enhancer 13; Enh 13) is critical for up-regulating SOX9.…”
Section: Sequencing Resultsmentioning
confidence: 99%
“…The authors identified significant RSPO1 down‐regulation in embryonic gonads at risk of canine XX DSD, without significant up‐regulation of SOX9 or other known testis pathway genes supposing that molecular lesions acting upstream of RSPO1 induce epigenomic gonadal mosaicism. The results of Salamon, Flisikowski, and Switonski () showed that methylation of SOX3 promoter region may play a role in canine XX DSD pathogenesis. As reported by Gonen et al (), the regulatory region of SOX9 is complex and that a single far‐upstream 557‐base pair element (Enhancer 13; Enh 13) is critical for up‐regulating SOX9 .…”
Section: Discussionmentioning
confidence: 99%
“…Persistent abnormal hypermethylation of the Sry gene (resulting in down-regulated mRNA and protein expression) was established as the cause of ovotestis and female phenotype in cloned Sry-positive XY dogs generated through somatic cell nuclear transfer (Jeong et al, 2016). In another example involving XX DSD dogs with ovotestis or testis phenotype, candidate gene promoter methylation bisulfite sequencing revealed hypomethylation in Sox9, hypermethylation in Wnt4 and hypermethylation of the Sox3 promoter at levels similar to that of control XY male dogs (Salamon et al, 2017). Both these examples show that epigenetic promoter methylation of important sex determination genes can be determinants of DSD in mammals.…”
Section: Epigeneticsmentioning
confidence: 99%